The Dynamics of Teacher-Student Interaction in Multicultural Classrooms: A Local Cultural Perspective in Border Schools of Kalimantan, NTT, and Papua - Christiana, Titi; Arintoko, Lasarus; Elviva, Starla; Rosella, Janet (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The cultural, linguistic, and ethnic diversity that characterizes Indonesia’s border regions presents both challenges and opportunities in the context of multicultural education. Schools in frontier, outermost, and underdeveloped (3T) areas serve as complex social interaction spaces where teachers and students from diverse cultural backgrounds engage in the teaching and learning process. This study aims to explore in depth the dynamics of interaction between teachers and students in multicultural classrooms in border areas and how local contexts shape the pedagogical strategies employed by teachers. Using a qualitative approach with an intrinsic case study design, data were collected through participatory observation, in-depth interviews, and documentation in primary and secondary schools in North Kalimantan, East Nusa Tenggara, and Papua. The results of the study show that teachers’ cultural sensitivity strongly influences successful classroom interaction, their ability to adapt to linguistic diversity, and contextual communication strategies that incorporate local wisdom. Teachers who can build inclusive pedagogical relationships create learning spaces that not only support student participation but also strengthen their cultural identity. This study contributes to the development of locally grounded multicultural pedagogical approaches and provides practical implications for teacher training and educational policy in 3T areas. The conclusion of this study emphasizes the importance of contextual sensitivity and a humanistic approach in fostering equitable and inclusive educational interactions amid diversity.